Self-assembled inorganic clusters of semiconducting quantum dots for effective solar hydrogen evolution. Issue 38 (26th April 2018) - Gao, Yu-Ji; Yang, Yichen; Li, Xu-Bing; Wu, Hao-Lin; Meng, Shu-Lin; Wang, Yang; Guo, Qing; Huang, Mao-Yong; Tung, Chen-Ho; Wu, Li-Zhu
Abstract : The catalytic activity of CdSe QDs could be enhanced more than 150-fold by forming self-assembled clusters with ZnSe QDs made ex situ . Abstract : Owing to promoted electron–hole separation, the catalytic activity of semiconducting quantum dots (QDs) towards solar hydrogen (H2 ) production has been significantly enhanced by forming self-assembled clusters with ZnSe QDs made ex situ . Taking advantage of the favored interparticle hole transfer to ZnSe QDs, the rate of solar H2 evolution of CdSe QDs can be increased to ∼30 000 μmol h −1 g −1 with ascorbic acid as the sacrificial reagent, ∼150-fold higher than that of bare CdSe QDs clusters under the same conditions.